10 steps to mastering stress : a lifestyle approach - Barlow, David H. (Oxford University Press, 2014)
We know that stress is bad for us. We see evidence of this in the news, we hear it from our doctors, and we feel it at the end of a hectic week. Health professionals have learned that stress interferes with our lives-it increases missed work days, can lead to relationship difficulties, and can increase the risk of turning to drugs and alcohol. It has also been shown that in some cases, chronic stress can increase our risk of developing certain serious illnesses. We know of all these negative effects that stress can cause, but, realistically, for most of us there's no end in sight-stressful eve.